Perbedaan Pengaruh Jahe, Aromaterapi Oil Lavender dan Musik Klasik terhadap Pengurangan Emesis Gravidarum pada Ibu Hamil Trimester I - Henik Istiqomah; Sri Wahyuni (Prodi D III Kebidanan Fakultas Ilmu Kesehatan Universitas Ibrahimy, 2024)
Emesis gravidarum is the most common disorder found in 70% of pregnant women. Nonpharmacological treatments that can be used are ginger, oil lavender aromatherapy, and classical music. The purpose of this study was to determine the differences in the effect of ginger, oil lavender aromatherapy, and classical music on reducing emesis gravidarum in the first trimester of pregnant women. The research method used a quasy-experiment with a three-group comparison pretest-posttest design in a time series. The sampling technique used purposive sampling, the sample size was 28 pregnant women in the working area of the Jogonalan II Health Center, 22 pregnant women in the Kebonarum Health Center, and 25 pregnant women in the Prambanan Health Center. Then divided into 3 groups, namely the ginger group, the oil lavender aromatherapy group, and the classical music group. Ginger reduced the emesis gravidarum score by 3,23. Oil lavender aromatherapy reduced the emesis gravidarum score by 4,42. Classical music lowers the emesis gravidarum score by 2,03. This study shows that there is an effect of reducing emesis gravidarum in first trimester pregnant women, but the difference in the effects is not significant because they have the same p value = 0,000 <0,05.ginger, oil lavender aromatherapy, classical music, emesis gravidarum